MODERN DIGITAL ADVANCEMENT IN SECOND LANGUAGE ACQUISITION - Uteniyazova Amina Sabirbaevna,; Ubbiniyazova Aygul Komekbaevna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This passage gives an overview of importance of modern approach in acquiring language skills. Their effectiveness, teaching methods and scientists’ ideas are given in this article as supportive examples.